OPERATING CAPACITY, PROFITABILITY, SALES GROWTH MEMENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR RITEL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021:SEBELUM DAN SEMASA PANDEMI COVID-19 - Azhar Shafa Putri Nabila; Vidiyanna Rizal Putri (Journal of Accounting, Management and Islamic Economics, 2024)
This study examines the effect of Operating Capacity, Profitability, Sales Growth on Financial Distress. This study compared two periods, namely the period before Covid-19 (2017-2019) and the period during Covid-19 (2019-2021). This study uses data from 21 retail sector companies listed on the Indonesia Stock Exchange. The sampling technique in this study used a purposive sampling technique with predetermined criteria. The research method used in this research is a multiple linear regression analysis technique using E-views 9 software. The results of this study indicate that Operating Capacity has no effect on Financial Distress in the period before Covid-19 (2017-2019) and during Covid-19 (2019-2021). Sales Growth had no effect on Financial Distress in the pre-Covid-19 period (2017-2019), but Sales Growth had a positive effect on Financial Distress during the Covid-19 period (2019-2021). Profitability has a negative effect on Financial Distress in the period before Covid-19 (2017-2019) and during Covid-19 (2019-2021).